The Mythologism and Mythopoeia in the Poetry of V. Bryusov - Arshakyan, Edgar (Bulletin of Yerevan University H: Russian Philology, 2022)
In the context of the problem of mythologism and mythopoeia in the poetry of V. Bryusov, the article analyzes two poems. On the example of the poem “The Death of Alexander”, the characteristic tendency of the synthesis of mythology and history of V. Bryusov's poetry is considered. The poem “The Thread of Ariadne” is considered from the point of view of mythopoeia in Bryusov's poetry. The general early symbolic context is also shown, within which, Bryusov’s mythopoeia develops. Particular attention is paid to the work “The Teachers of the Teachers”, which reveals the role of myth in the artistic consciousness of the poet.
Keywords: V. Bryusov; symbolism; mythologism; mythopoeia; “The Teachers of the Teachers”; “The Death of Alexander”; “The Ariadne's Thread”